AN ANALYSIS OF THE MAIN CHARACTER’S CONFLICT IN THE MOVIE ACT’S OF VENGEANCE - Maku, Serfus Evander; Jayantini, I Gusti Agung Sri Rwa; Juniartha, I Wayan (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThe aim this study is to describe the conflict of the main character Act of Vengeance in the movie.This study focused on explaining the types of conflicts that the main character faced in the movieAct of Vengeance and to analyze how the main character manages to settle conflict in the movieAct of Vengeance. The collected data were analyzed descriptively based on Kenney’s theory ofliterature (1966). The result of this study reveals that the conflicts faced by the main character canbe divided into internal conflict and external conflict. The sources of conflicts faced by the maincharacter are different opinions, incompatible roles, incompatible goals, limited resources. Theconflict management strategies applied are pacification, compromise, and creative integration.Conflict adds excitement and suspense to a story. As the plot unfolds, the readers start to wonderwhat will happen next, and how the character will handle the situation. It can be concluded thatthe conflict of the main character has important roles in created the movie story.Keywords: Main character, Movie, and conflict.ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan konflik karakter utama Act of Vengeance dalamfilm tersebut. Penelitian ini difokuskan untuk menjelaskan jenis-jenis konflik yang dihadapi tokohutama dalam film Act of Vengeance dan menganalisis bagaimana tokoh utama mengelola konflikdalam film Act of Vengeance. Data yang terkumpul dianalisis secara deskriptif berdasarkan teorisastra Kenney (1966). Hasil penelitian ini mengungkapkan bahwa konflik yang dihadapi olehtokoh utama dapat dibagi menjadi konflik internal dan konflik eksternal. Sumber konflik yangdihadapi oleh tokoh utama adalah perbedaan pendapat, peran yang tidak sesuai, tujuan yangtidak sesuai, sumber daya yang terbatas. Strategi manajemen konflik yang diterapkan adalahpasifikasi, kompromi, dan integrasi kreatif. Konflik menambah kegembiraan dan ketegangan padasebuah cerita. Saat plot terungkap, pembaca mulai bertanya-tanya apa yang akan terjadiselanjutnya, dan bagaimana karakter akan menangani situasi tersebut. Dapat disimpulkan bahwakonflik tokoh utama memiliki peran penting dalam pembuatan cerita film.Kata kunci: Tokoh utama, Film, dan konflik.